Ghazi Barotha project on Indus River in Pakistan - Shaikh, Illahi B., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
In order to use the available water from the Indus River and use the natural head of 76 meters available in the area, the Government of Pakistan has constructed the Ghazi Barotha Project on the Indus River through the Water and Power Development Authority (WAPDA), which also produces 1450 MW of hydropower. The project is running successfully with minimal environmental disruptions and has properly addressed resettlement issues in consultation with donors. This paper describes the Ghazi Barotha Project in Pakistan.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.